Electrode and power storage device
Patent Information
- Application Number
- JP2021009068
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-22
- Publication Date
- 2025-03-06
- Estimated Expiration
- 2041-01-22
AI Technical Summary
【0014】 本発明によれば、電子抵抗を減少させるとともに、耐久性を向上させることが可能な電極を提供することができる。
Smart Images

Figure 0007641126000001 
Figure 0007641126000002 
Figure 0007641126000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode and an electricity storage device. [Background technology]
[0002] Conventionally, lithium ion secondary batteries have been widely used as a storage device having a high energy density. The lithium ion secondary battery has a structure in which, for example, a separator is present between a positive electrode and a negative electrode, and an electrolyte is filled. In addition, all-solid-state batteries using an inorganic solid electrolyte instead of an electrolyte are also known.
[0003] Such lithium ion secondary batteries have various requirements depending on the application, and for example, when used in automobiles, etc., there is a demand for further improvement in the volumetric energy density. To meet this demand, a method of increasing the packing density of the electrode active material can be mentioned.
[0004] As a method for increasing the packing density of the electrode active material, it has been proposed to use a metal foam as the current collector constituting the positive and negative electrodes (see Patent Documents 1 and 2). A metal foam has a mesh structure with uniform pore diameters and a large surface area. Therefore, by filling the voids in the metal foam with an electrode mixture containing the electrode active material, the amount of electrode active material per unit area of the electrode can be increased. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 7-099058 [Patent Document 2] Japanese Patent Application Publication No. 8-329954 Summary of the Invention [Problem to be solved by the invention]
[0006] However, in the case of a current collector that does not incorporate a foam metal electrode composite, the amount of metal is extremely small relative to the current collector foil, resulting in an increase in electronic resistance. In particular, when a large current is passed through the current collector, the supply of electrons from the current collector is insufficient, resulting in a significant increase in electronic resistance. Furthermore, there is a problem that the strength of the welded parts and current collectors is insufficient, making them prone to breakage and reducing durability.
[0007] An object of the present invention is to provide an electrode capable of reducing electronic resistance and improving durability. [Means for solving the problem]
[0008] One aspect of the present invention is an electrode having a current collector, an electrode composite, and an electrode tab, the current collector being a metal porous body having a region A and a region B having a smaller porosity than region A, the electrode composite being filled into the voids of region A, and the electrode tab being fixed to region B, the region A having a region A1 and a region A2 having a smaller porosity than region A1, and the region A2 being at a greater distance from the electrode tab than region A1.
[0009] The region B may have a region B1 to which the electrode tab is fixed and a region B2 to which the electrode tab is not fixed, and the porosity of the region B1 may be smaller than the porosity of the region A.
[0010] The region A may further include a region A3 connecting the region A2 and the region B, and the porosity of the region A3 may be smaller than the porosity of the region A1.
[0011] The region A further includes a region A3 connecting the region A2 and the region B, and the porosity of the region A1, the porosity of the region A2, the porosity of the region A3, the porosity of the region B1, and the porosity of the region B2 are each ε A1 , ε A2 , ε A3 , ε B1 and ε B2 Then, the formula εA1 >ε A3 ≧ε A2 >ε B2 ≧ε B1 may be satisfied.
[0012] The current collector may be substantially rectangular.
[0013] Another embodiment of the present invention is an energy storage device that includes the above-described electrode. Effect of the Invention
[0014] According to the present invention, it is possible to provide an electrode that can reduce electronic resistance and improve durability. [Brief description of the drawings]
[0015] [Figure 1] FIG. 2 is a diagram showing an example of an electrode according to the present embodiment. [Diagram 2] FIG. 2 is a diagram showing a current collector corresponding to the electrode of FIG. [Diagram 3] 1. FIG. 4 is a diagram showing another example of a current collector corresponding to the electrode of FIG. [Figure 4] FIG. 2 is a diagram showing evaluation results of initial cell resistance of the lithium ion secondary batteries of Example 1 and Comparative Example 1. [Diagram 5] FIG. 2 is a diagram showing the evaluation results of the C rate characteristics of the lithium ion secondary batteries of Example 1 and Comparative Example 1. [Figure 6] FIG. 2 is a diagram showing the evaluation results of the capacity retention rates of the lithium ion secondary batteries of Example 1 and Comparative Example 1. [Figure 7] FIG. 2 is a diagram showing the evaluation results of the resistance change rate of electronic resistance (0.1 S) of the lithium ion secondary batteries of Example 1 and Comparative Example 1. [Figure 8] FIG. 2 is a diagram showing the evaluation results of the rate of resistance change of the reaction resistance (1S) of the lithium ion secondary batteries of Example 1 and Comparative Example 1. [Figure 9] FIG. 2 is a diagram showing evaluation results of the resistance change rate of ion diffusion resistance (10S) of the lithium ion secondary batteries of Example 1 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be described with reference to the drawings.
[0017] <Electrode> An example of an electrode according to the present embodiment is shown in Fig. 1. Also, a current collector corresponding to the electrode in Fig. 1 is shown in Fig. 2.
[0018] The electrode 10 has a current collector 11, an electrode mixture 12, and an electrode tab 13. The current collector 11 is a porous metal body having a region A and a region B having a smaller porosity than region A (see FIG. 2). In the electrode 10, the voids in region A of the current collector 11 are filled with an electrode mixture 12, and an electrode tab 13 is fixed to region B of the current collector 11. Region A of the current collector 11 has region A1 and region A2 having a smaller porosity than region A1, and region A2 is farther from the electrode tab than region A1.
[0019] In electrode 10, the porosity of region B of current collector 11 is smaller than the porosity of region A of current collector 11, so that the electronic conductivity between electrode mixture 12 and electrode tab 13 is improved, and as a result, the electronic resistance is reduced. Furthermore, the strength of region B is improved, and breakage or cracking of electrode 10 is suppressed, thereby improving durability.
[0020] In addition, in electrode 10, the porosity of region A2 of current collector 11 is smaller than the porosity of region A1 of current collector 11, so that electronic conductivity to the end of region A2 is improved, and as a result, electronic resistance is reduced. This is particularly advantageous when electrode 10 is made larger and longer.
[0021] The porosity of region A of current collector 11 is preferably 85% or more and 99% or less, and more preferably 90% or more and 98% or less.
[0022] The porosity of region B of current collector 11 is preferably 1% or more and 50% or less, and more preferably 1% or more and 10% or less.
[0023] The porosity of region A1 of current collector 11 is preferably 93% or more and 99% or less, and more preferably 95% or more and 98% or less.
[0024] The porosity of region A2 of current collector 11 is preferably 90% or more and 97% or less, and more preferably 90% or more and 93% or less.
[0025] Region B of current collector 11 has region B1 to which electrode tab 13 is fixed and region B2 to which electrode tab 13 is not fixed, and the porosity of region B1 may be smaller than the porosity of region A. This further improves the electronic conductivity between electrode mixture 12 and electrode tab 13.
[0026] In this specification and claims, the region B1 where the electrode tab is fixed is a region where the electrode tab exists when the current collector to which the electrode tab is fixed is viewed from above from the side where the electrode tab is fixed, and includes a region where the electrode tab is not actually formed. Also, the region B2 where the electrode tab is not fixed is a region where no electrode tab exists when viewed from above in the same manner as above.
[0027] The porosity of region B1 of current collector 11 is preferably 1% or more and 50% or less, and more preferably 1% or more and 10% or less.
[0028] The porosity of region B2 of current collector 11 is preferably 5% or more and 50% or less, and more preferably 5% or more and 20% or less.
[0029] Region A of current collector 11 further includes region A3 connecting region A2 of current collector 11 with region B of current collector 11, and the porosity of region A3 may be smaller than the porosity of region A1 (see FIG. 3). This further improves electronic conductivity to the end of region A2, and as a result, further reduces electronic resistance.
[0030] In the case where the region A of the current collector 11 further includes a region A3, the porosity of the region A1, the porosity of the region A2, the porosity of the region A3, the porosity of the region B1, and the porosity of the region B2 of the current collector 11 are respectively defined as ε A1 , ε A2 , ε A3 , ε B1 and ε B2 Then, the formula ε A1 >ε A3 ≧ε A2 >ε B2 ≧ε B1 This further improves the electronic conductivity to the end of the region A2, and as a result, the electronic resistance is further reduced.
[0031] The porosity of region A3 of current collector 11 is preferably 90% or more and 98% or less, and more preferably 93% or more and 95% or less.
[0032] The current collector 11 is obtained, for example, by appropriately pressing a metal porous body before and after filling with the electrode mixture 12 to form the regions A (A1, A2, A3) and the regions B (B1, B2).
[0033] The shape of the current collector 11 is not particularly limited, but examples thereof include a substantially rectangular parallelepiped shape.
[0034] In this specification and claims, a substantially rectangular parallelepiped includes a rectangular parallelepiped that has chamfered edges.
[0035] Here, the chamfering may be either C-chamfering or R-chamfering.
[0036] [Porous metal body] The metal porous body is not particularly limited as long as it is a metal porous body whose pores can be filled with an electrode mixture, and examples thereof include foamed metal.
[0037] Metal foam has a network structure and a large surface area. By using metal foam as a current collector, the voids of the metal foam can be filled with an electrode mixture, the amount of electrode active material per unit area of the electrode can be increased, and the volumetric energy density of the secondary battery can be improved. In addition, since the electrode mixture can be easily fixed, a thick film of the electrode mixture can be formed without thickening the slurry used for coating the electrode mixture. In addition, the binder required for thickening the slurry can be reduced. Therefore, a thick film of the electrode mixture with low resistance can be formed compared to the case where a metal foil is used as a current collector. Therefore, the capacity per unit area of the electrode can be increased, which contributes to the high capacity of the secondary battery.
[0038] Examples of metals constituting the metal porous body include nickel, aluminum, stainless steel, titanium, copper, silver, nickel-chromium alloy, etc. Among these, the metal porous body constituting the positive electrode current collector is preferably aluminum foam, and the metal porous body constituting the negative electrode current collector is preferably copper foam or nickel foam.
[0039] [Electrode composite material] The electrode mixture contains an electrode active material and may further contain other components.
[0040] Examples of the other components include a solid electrolyte, a conductive assistant, and a binder.
[0041] The positive electrode active material contained in the positive electrode mixture is not particularly limited as long as it is capable of absorbing and releasing lithium ions. For example, LiCoO2, Li(Ni 5 / 10 Co 2 / 10 Mn 3 / 10 )O 2、 Li(Ni) 6 / 10 Co 2 / 10 Mn 2 / 10 )O 2、 Li(Ni) 8 / 10 Co 1 / 10 Mn 1 / 10 )O 2、 Li(Ni) 0.8 Co 0.15Al 0.05 )O 2、 Li(Ni) 1 / 6 Co 4 / 6 Mn 1 / 6 )O 2、 Li(Ni) 1 / 3 Co 1 / 3 Mn 1 / 3 )O 2、 Examples include LiCoO4, LiMn2O4, LiNiO2, LiFePO4, lithium sulfide, and sulfur.
[0042] The negative electrode active material contained in the negative electrode mixture is not particularly limited as long as it is capable of absorbing and releasing lithium ions. Examples of the negative electrode active material include metallic lithium, lithium alloys, metal oxides, metal sulfides, metal nitrides, Si, SiO, and carbon materials.
[0043] Examples of carbon materials include artificial graphite, natural graphite, hard carbon, and soft carbon.
[0044] [Electrode tab] The electrode tab is not particularly limited, and any known electrode tab can be used.
[0045] <Electrode manufacturing method> The method for producing the electrode of the present embodiment is not particularly limited, and a method commonly used in this technical field can be applied.
[0046] The method for filling the gaps in region A of the current collector with the electrode mixture is not particularly limited, but examples thereof include a method in which a plunger-type die coater is used to apply pressure to fill a slurry containing the electrode mixture into the gaps in region A of the current collector.
[0047] Another method for filling the gaps in region A of the current collector with the electrode mixture includes a method in which a pressure difference is generated between the surface of the current collector on which the electrode mixture is introduced and the opposite surface, and the pressure difference causes the electrode mixture to penetrate and fill the gaps in region A of the current collector. In this case, the nature of the electrode mixture to be introduced is not particularly limited, and it may be a powder of the electrode mixture or a liquid such as a slurry containing the electrode mixture.
[0048] After the electrode mixture is filled into the voids in region A of the current collector, a method generally used in the art can be applied. For example, the current collector with the electrode mixture filled in region A is dried, pressed, and an electrode tab is welded to obtain an electrode. At this time, the porosity of the current collector and the density of the electrode mixture can be adjusted by pressing.
[0049] When the current collector in which region A is filled with the electrode mixture is pressed, the current collector is compressed uniformly by pressing, so the relationship in magnitude of the porosity in each region of the current collector does not change.
[0050] <Electricity storage device> The electricity storage device of this embodiment has the electrode of this embodiment.
[0051] Examples of the power storage device include secondary batteries such as lithium ion secondary batteries, and capacitors.
[0052] The lithium ion secondary battery may be a battery having a liquid electrolyte or a battery having a solid or gel electrolyte, and the solid or gel electrolyte may be either organic or inorganic.
[0053] The electrode of this embodiment may be applied only to the positive electrode, only to the negative electrode, or to both the positive electrode and the negative electrode.
[0054] When the electrode of this embodiment is applied to a lithium ion secondary battery, it is particularly advantageous when the electrode of this embodiment is applied to a positive electrode, since the negative electrode active material has high electronic conductivity.
[0055] [Lithium-ion secondary battery] The lithium ion secondary battery of the present embodiment includes a positive electrode, a negative electrode, and a separator or a solid electrolyte layer located between the positive electrode and the negative electrode. In the lithium ion secondary battery of the present embodiment, at least one of the positive electrode and the negative electrode is the electrode of the present embodiment.
[0056] In the lithium ion secondary battery of this embodiment, the positive electrode or negative electrode to which the electrode of this embodiment is not applied is not particularly limited as long as it functions as a positive electrode or negative electrode of the lithium ion secondary battery.
[0057] In the lithium ion secondary battery of this embodiment, two types of materials are selected from materials capable of forming electrodes, and the charge / discharge potentials of the two types of materials are compared. The material exhibiting a more noble potential is applied to the positive electrode, and the material exhibiting a more base potential is applied to the negative electrode, thereby making it possible to form any battery.
[0058] When the lithium ion secondary battery of this embodiment includes a separator, the separator is located between the positive electrode and the negative electrode.
[0059] The separator is not particularly limited, and any known separator that can be applied to lithium ion secondary batteries can be used.
[0060] When the lithium ion secondary battery of this embodiment includes a solid electrolyte layer, the solid electrolyte layer is located between the positive electrode and the negative electrode.
[0061] The solid electrolyte contained in the solid electrolyte layer is not particularly limited, and may be any material capable of conducting lithium ions between the positive electrode and the negative electrode.
[0062] Examples of the solid electrolyte include oxide-based electrolytes and sulfide-based electrolytes. EXAMPLES
[0063] Examples of the present invention will be described below, but the present invention is not limited to these examples. <Example 1>
[0064] [Preparation of positive electrode] (Processing of porous metal bodies) The metal porous body has dimensions of 30 mm in length, 40 mm in width, 1 mm in height, porosity of 97%, number of cells of 46 per inch, pore diameter of 0.5 mm, and specific surface area of 5000 m 2 / m 3 An aluminum foam having a substantially rectangular parallelepiped shape was prepared.
[0065] A sheet of foamed aluminum was pressed onto the end of the foamed aluminum on the side where the electrode tab was fixed, and the porosity of region B was adjusted to 5%. In addition, the end of the foamed aluminum on the side where the electrode tab was not fixed was pressed, and the porosity of region A2 was adjusted to 95%, to obtain a processed metal porous body.
[0066] The porosity of the porous metal body was calculated by the following method. First, the thickness of the sample obtained by punching out each region of the porous metal body into a circle with a diameter of 16 mm was measured, and the volume of the sample was calculated. Next, the mass of the sample was measured, and the density of the sample was calculated. Finally, the ratio of the density of the sample to the true density of the metal constituting the porous metal body was calculated, and this was taken as the porosity of the sample.
[0067] (Preparation of positive electrode mixture slurry) As the positive electrode active material, LiNi 0.5 Co 0.2 Mn 0.3 O2 was prepared.
[0068] 94% by mass of the positive electrode active material, 4% by mass of carbon black as a conductive assistant, and 2% by mass of polyvinylidene fluoride (PVDF) as a binder were mixed, and the resulting mixture was dispersed in an appropriate amount of N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode composite slurry.
[0069] (Filling of positive electrode mixture) Using a plunger type die coater, the coating amount was 90mg / cm 2The positive electrode composite slurry was applied to a processed porous metal body so that the positive electrode composite was filled, and then dried at 120°C for 12 hours under vacuum conditions. Next, the processed porous metal body filled with the positive electrode composite was roll-pressed at a pressure of 15 tons to obtain a positive electrode current collector filled with the positive electrode composite. Next, an electrode tab was welded to region B of the positive electrode current collector filled with the positive electrode composite to produce a positive electrode. The electrode composite constituting the obtained positive electrode had a basis weight of 90 mg / cm. 2 , density 3.2g / cm 3 The prepared positive electrode was punched out to a size of 3 cm x 4 cm.
[0070] [Preparation of negative electrode] (Preparation of negative electrode mixture slurry) 96.5% by mass of natural graphite, 1% by mass of carbon black as a conductive assistant, 1.5% by mass of styrene butadiene rubber (SBR) as a binder, and 1% by mass of sodium carboxymethylcellulose (CMC) as a thickener were mixed, and then the resulting mixture was dispersed in an appropriate amount of distilled water to prepare a negative electrode composite slurry.
[0071] (Formation of negative electrode mixture layer) As a negative electrode current collector, a copper foil having a thickness of 8 μm was prepared. Using a die coater, the coating amount was 45mg / cm 2 The negative electrode composite slurry was applied to a current collector so that the negative electrode composite layer had a mass per unit area of 45 mg / cm2, and then dried at 120°C for 12 hours under vacuum conditions. Next, the current collector on which the negative electrode composite layer was formed was roll-pressed at a pressure of 10 tons to produce a negative electrode. The electrode composite layer constituting the obtained negative electrode had a mass per unit area of 45 mg / cm2. 2 , density is 1.5g / cm 3 The negative electrode was punched out to a size of 3 cm x 4 cm.
[0072] [Preparation of lithium-ion secondary batteries] As a separator, a microporous membrane having a thickness of 25 μm and a three-layer laminate of polypropylene / polyethylene / polypropylene was prepared and punched out to a size of 3 cm×4 cm.
[0073] The aluminum laminate for secondary batteries was heat sealed and processed into a bag shape, and then a laminate having a positive electrode, a negative electrode and a separator disposed between them was inserted into the processed product to prepare a laminate cell.
[0074] As an electrolyte, a solution was prepared by dissolving 1.2 mol of LiPF6 in a solvent mixed with ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 3:4:3.
[0075] An electrolyte was injected into the laminate cell to prepare a lithium ion secondary battery.
[0076] <Comparative Example 1> A lithium ion secondary battery was produced in the same manner as in Example 1, except that the metal porous body was used as it was without being processed when producing the positive electrode.
[0077] <Evaluation of initial characteristics of lithium-ion secondary batteries> The lithium ion secondary batteries of Example 1 and Comparative Example 1 were evaluated for the following initial characteristics.
[0078] [Initial discharge capacity] The lithium ion secondary battery was left at the measurement temperature (25°C) for 3 hours, and then constant current charging was performed at 0.33C to 4.2V, followed by constant voltage charging at a voltage of 4.2V for 5 hours. Next, the lithium ion secondary battery was left for 30 minutes, and then discharged at a discharge rate of 0.33C to 2.5V, and the discharge capacity was measured. The obtained discharge capacity was taken as the initial discharge capacity.
[0079] [Initial cell resistance] The lithium ion secondary battery after measuring the initial discharge capacity was adjusted to a charge level (SOC (State of Charge)) of 50%. Next, it was discharged for 10 seconds at a current value of 0.2C, and the voltage was measured 10 seconds after the discharge was completed. Next, the lithium ion secondary battery was left for 10 minutes, and then supplementary charging was performed to return the SOC to 50%, and the lithium ion secondary battery was left for 10 minutes. Next, the above operation was performed at each C rate of 0.5C, 1C, 1.5C, 2C, and 2.5C, and the results were plotted with the horizontal axis representing the current value and the vertical axis representing the voltage. The slope of the approximation line obtained from the plot was taken as the initial cell resistance of the lithium ion secondary battery.
[0080] FIG. 4 shows the evaluation results of the initial cell resistance of the lithium ion secondary batteries of Example 1 and Comparative Example 1.
[0081] It can be seen from FIG. 4 that the lithium ion secondary battery of Example 1 has a smaller initial cell resistance (particularly, electronic resistance) than the lithium ion secondary battery of Comparative Example 1.
[0082] [C rate characteristics] After measuring the initial discharge capacity, the lithium-ion secondary battery was left at the measurement temperature (25°C) for 3 hours, and then constant current charging was performed at 0.33 C to 4.2 V, followed by constant voltage charging for 5 hours at a voltage of 4.2 V. Next, the lithium-ion secondary battery was left for 30 minutes, and then discharged to 2.5 V at a discharge rate of 0.5 C (C rate), and the initial discharge capacity was measured.
[0083] The above operation was carried out at C rates of 0.33C, 1C, 1.5C, 2C, and 2.5C, and the initial discharge capacity at each C rate was converted into a capacity retention rate when the initial discharge capacity at 0.33C was taken as 100%, to obtain the C rate characteristics.
[0084] FIG. 5 shows the evaluation results of the C-rate characteristics of the lithium ion secondary batteries of Example 1 and Comparative Example 1.
[0085] It can be seen from FIG. 5 that the lithium ion secondary battery of Example 1 has a larger capacity retention rate than the lithium ion secondary battery of Comparative Example 1.
[0086] <Evaluation of post-durability characteristics of lithium-ion secondary batteries> The lithium ion secondary batteries of Example 1 and Comparative Example 1 were subjected to the following evaluation of post-durability characteristics.
[0087] [Discharge capacity after durability] In a thermostatic chamber at 45°C, the lithium ion secondary battery was charged at a constant current of 0.6C to 4.2V, followed by constant voltage charging at a voltage of 4.2V for 5 hours or until the current value reached 0.1C. Next, the lithium ion secondary battery was left for 30 minutes, and then discharged at a constant current of 0.6C to 2.5V, and the operation of leaving the battery for 30 minutes was repeated 100 cycles. Next, in a thermostatic chamber at 25°C, the lithium ion secondary battery was left for 24 hours in a state after discharging to 2.5V, and then the discharge capacity after durability was measured in the same manner as the initial discharge capacity. This operation was repeated every 100 cycles, and the discharge capacity after durability was measured up to 500 cycles.
[0088] [Cell resistance after durability] After 500 cycles in the measurement of the post-endurance discharge capacity were completed, the charge level (SOC (State of Charge)) was adjusted to 50%, and the post-endurance cell resistance was determined in the same manner as the initial cell resistance.
[0089] [Capacity maintenance rate] The ratio of the discharge capacity after endurance for every 100 cycles to the initial discharge capacity was calculated and defined as the capacity retention rate for each cycle.
[0090] FIG. 6 shows the evaluation results of the capacity retention rates of the lithium ion secondary batteries of Example 1 and Comparative Example 1.
[0091] It can be seen from FIG. 6 that the lithium ion secondary battery of Example 1 has a larger capacity retention rate over 200 to 500 cycles than the lithium ion secondary battery of Comparative Example 1.
[0092] [Resistance change rate] The ratio of the cell resistance after the endurance test to the initial cell resistance was calculated and defined as the resistance change rate.
[0093] FIG. 7 shows the evaluation results of the resistance change rate of the electronic resistance (0.1 S) of the lithium ion secondary batteries of Example 1 and Comparative Example 1.
[0094] FIG. 8 shows the evaluation results of the resistance change rate of the reaction resistance (1S) of the lithium ion secondary batteries of Example 1 and Comparative Example 1.
[0095] FIG. 9 shows the evaluation results of the resistance change rate of the ion diffusion resistance (10S) of the lithium ion secondary batteries of Example 1 and Comparative Example 1.
[0096] 7 to 9 show that the lithium ion secondary battery of Example 1 has smaller resistance change rates in electronic resistance (0.1 S) and ion diffusion resistance (10 S) over 500 cycles than the lithium ion secondary battery of Comparative Example 1.
[0097] From the above, it is understood that the positive electrode of Example 1 has higher durability than the positive electrode of Comparative Example 1. [Explanation of symbols]
[0098] 10 electrodes 11 Current collector 12 Electrode mixture 13 Electrode tab
Claims
1. The electrode assembly includes a current collector, an electrode mixture, and an electrode tab, The current collector is a metal porous body having a region A and a region B having a smaller porosity than the region A, The gap in the region A is filled with the electrode mixture, The electrode tab is fixed to the region B, The region A has a region A1 and a region A2 having a smaller porosity than the region A1, The area A2 is located at a greater distance from the electrode tab than the area A1. The region B has a region B1 to which the electrode tab is fixed and a region B2 to which the electrode tab is not fixed, An electrode, wherein the porosity of the region B1 is equal to or less than the porosity of the region B2 and is smaller than the porosity of the region A.
2. The region A further includes a region A3 connecting the region A2 and the region B, The electrode of claim 1 , wherein the porosity of the region A3 is less than the porosity of the region A1 .
3. The porosity of the region A1, the porosity of the region A2, the porosity of the region A3, the porosity of the region B1, and the porosity of the region B2 are each ε A1 , ε A2 , ε A3 , ε B1 and ε B2 Then, the formula e A1 >e A3 ≧e A2 >e B2 ≧e B1 The electrode according to claim 2 ,
4. The electrode according to claim 1 , wherein the current collector is substantially rectangular.
5. An electricity storage device comprising the electrode according to claim 1 .
Citation Information
Patent Citations
Electrode structure for secondary battery
JP1995099058A
Electrode plate for battery and manufacture thereof
JP1996329954A
Three-dimensional porous aluminum mesh for use in collector, and collector, electrode, nonaqueous-electrolyte battery, capacitor, and lithium-ion capacitor using said porous aluminum
WO2012111657A1